Comparative study to evaluate the effect of vibrations on human subjects with different masses and anthropometric dimensions using a four-layer CAD model - Sharma, Shubham; Kalsi, Sachin; Singh, Jagjit; Singh, Ishbir (Research on biomedical engineering, 2024)
Purpose Vibrations encountered in variant environmental conditions can lead to fatigue, discomfort, and health risks to individuals who come into contact with them. Understanding the effect of vibration on human subjects of different masses and anthropometric dimensions is crucial for ergonomic designing and minimizing the potential adverse effects. Materials and methods This study presents a comparative study to evaluate the impact of these vibrations on Indian human subjects with masses of 54 kg and 76 kg, using a four-layer CAD model with the help of FEM simulations to analyze the seat-to-head (STHT) and feet-to-head (FTHT) transmissibility for vibrations within the frequency of 0–20 Hz range and acceleration of different intensities, i.e., 0.5 m/s 2 , 1 m/s 2 , and 1.5 m/s 2 . The four-layer CAD model considered four anatomical layers of a human subject including skin, organs, bones, and muscles; each layer was assigned appropriate material properties as per the characteristics of a human tissue. Results There were significant differences in the STHT and FTHT for both human subjects, and the pattern of transmissibility varied across the frequency range and was also influenced by the levels of acceleration. The higher level of acceleration results in an increase in transmissibility, and the increase in the mass of human subjects also shows the increase in the value of transmissibility that represents the pronounced impact of vibrations on human subjects. Conclusion The findings indicate that body mass has a major impact on vibration transmission. The relationship between body mass and transmissibility, on the other hand, is complicated and can change depending on the vibration transmission channel. These findings add to the increasing body of information in the field of human vibration exposure and may have implications for building more personalized seating and ergonomic solutions for people with varied body types. More study is needed to go deeper into the underlying processes as well as to investigate the possible applicability of these results in occupational and ergonomic contexts.